Temperature and bias-voltage dependence of atomic-layer-deposited HfO2-based magnetic tunnel junctions - Fabretti, Savio; Zierold, Robert; Nielsch, Kornelius; Voigt, Carmen; Ronning, Carsten; Peretzki, Patrick; Seibt, Michael; Thomas, Andy (Applied Physics Letters, 2014)
Magnetic tunnel junctions with HfO2 tunnel barriers were prepared through a combination of magnetron sputtering and atomic layer deposition. We investigated the tunneling transport behavior, including the tunnel magnetoresistance ratio and the current-voltage characteristics between room temperature and 2K. Here, we achieved a tunneling magneto resistance ratio of 10.3% at room temperature and 19.3% at 2K. Furthermore, we studied the bias-voltage and temperature dependencies and compared the results with those of commonly used alumina- and magnesia-based magnetic tunnel junctions. We observed a polycrystalline/amorphous electrode-barrier system via high-resolution transmission electron microscopy.
CRIS-Team Scopus Importer:2023-03-20